2002
DOI: 10.1002/14651858.cd004721
|View full text |Cite
|
Sign up to set email alerts
|

Palliation of metastatic bone pain: single fraction versus multifraction radiotherapy

Abstract: Single fraction radiotherapy was as effective as multifraction radiotherapy in relieving metastatic bone pain. However, the re-treatment rate and pathological fracture rates were higher after single fraction radiotherapy. Studies with quality of life and health economic end points are warranted to find out the optimal treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 58 publications
3
56
0
6
Order By: Relevance
“…52,54 However, all studies reported that more retreatments were given after single-fraction radiotherapy. 53 This higher retreatment regimen seems to reflect more the uncertainty of both radiation oncologist and patient on the effect of such a "simple" treatment than its true ineffectiveness since patients who were treated by a single fraction were retreated with lower pain scores. 40,57 An ongoing prospectively randomized trial is currently studying the effectiveness of retreatment after single-and multiplefraction radiotherapy using different treatment schedules.…”
Section: External Beam Radiotherapy: Painmentioning
confidence: 99%
See 1 more Smart Citation
“…52,54 However, all studies reported that more retreatments were given after single-fraction radiotherapy. 53 This higher retreatment regimen seems to reflect more the uncertainty of both radiation oncologist and patient on the effect of such a "simple" treatment than its true ineffectiveness since patients who were treated by a single fraction were retreated with lower pain scores. 40,57 An ongoing prospectively randomized trial is currently studying the effectiveness of retreatment after single-and multiplefraction radiotherapy using different treatment schedules.…”
Section: External Beam Radiotherapy: Painmentioning
confidence: 99%
“…A single dose of 8 Gy has gained widespread acceptance, with response rates for pain of 60%. [52][53][54] For painful spinal metastases specifically, response percentages of 73% were reported in 342 patients who were treated within a randomized trial comparing single fraction of 8 Gy versus 24 Gy in 6 fractions. 47 If the diagnostic radiological investigations show extensive bone destruction, more irradiation (Ͼ25 Gy) is usually applied to induce remineralization and, hence, strengthening of the involved bone.…”
Section: External Beam Radiotherapy: Painmentioning
confidence: 99%
“…During recent years, more attention has been directed towards improved palliative care for cancer patients with skeletal metastases. Radiotherapy remains the mainstay for painful skeletal metastases (Sze et al 2003), but hormone therapy, chemotherapy, and biphosphonates (Diel et al 2004, Pavlakis et al 2005 are also important treatment modalities. The aim of surgical treatment is to restore function while alleviating pain.…”
Section: The Scandinavian Sarcoma Group Skeletal Metastasis Registrymentioning
confidence: 99%
“…Following low-dose conventional external beam palliative radiotherapy (cEBRT), 1 several randomized trials and meta-analyses have confirmed complete and overall pain response rates ranging from ∼10% to 30% and 50% to 70%, respectively. 2 …”
mentioning
confidence: 99%